2004
DOI: 10.1002/art.20124
|View full text |Cite
|
Sign up to set email alerts
|

The role of subchondral bone remodeling in osteoarthritis: Reduction of cartilage degeneration and prevention of osteophyte formation by alendronate in the rat anterior cruciate ligament transection model

Abstract: Objective. It has been suggested that subchondral bone remodeling plays a role in the progression of osteoarthritis (OA). To test this hypothesis, we characterized the changes in the rat anterior cruciate ligament transection (ACLT) model of OA and evaluated the effects of alendronate (ALN), a potent inhibitor of bone resorption, on cartilage degradation and on osteophyte formation.Methods. Male Sprague-Dawley rats underwent ACLT or sham operation of the right knee. Animals were then treated with ALN (0.03 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
471
7
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(531 citation statements)
references
References 60 publications
38
471
7
15
Order By: Relevance
“…In a guinea pig model, bone densitometry evaluation following meniscectomy revealed typical variations in bone metabolism with early resorption of subchondral bone followed by increased bone density [18]. This concurs with findings from other animal models, such as the ACL dog and rat OA models, in which were observed, at an early stage of the disease process, increased subchondral bone resorption with trabecular thickness reduction and an increased number of osteoclasts, as well as increased production of catabolic factors including cathepsin K and matrix metalloproteinase (MMP)-13 [6][7][8][9].…”
Section: Correlation Between In Vivo Findings In Animals and Human Oasupporting
confidence: 82%
See 2 more Smart Citations
“…In a guinea pig model, bone densitometry evaluation following meniscectomy revealed typical variations in bone metabolism with early resorption of subchondral bone followed by increased bone density [18]. This concurs with findings from other animal models, such as the ACL dog and rat OA models, in which were observed, at an early stage of the disease process, increased subchondral bone resorption with trabecular thickness reduction and an increased number of osteoclasts, as well as increased production of catabolic factors including cathepsin K and matrix metalloproteinase (MMP)-13 [6][7][8][9].…”
Section: Correlation Between In Vivo Findings In Animals and Human Oasupporting
confidence: 82%
“…Moreover, in this animal model, the severity of cartilage fibrillation and loss generally exceeds bone changes only in advanced OA. Although it has been shown in some induced OA animal models, which allow chronological analysis of the disease progression, that the subchondral bone changes precede cartilage changes [6][7][8][9], this has yet to be clarified in humans.…”
Section: Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have also indicated that bone resorption inhibitors suppress OA progression. (4,5) Several bone turnoverinhibiting drugs, such as alendronate, risedronate, and calcitonin, have been proposed as candidates for OA treatment. (6,7) Therefore, it is important to understand subchondral bone turnover to analyze OA pathophysiology and develop appropriate therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The main causes of OA are considered to be aging and excessive mechanical stress to the joints, due to joint instability or obesity (2). A number of in vivo studies using various joint instability models have clarified some aspects of the molecular mechanisms comprising the response to excessive mechanical stress to the joints (3)(4)(5)(6)(7)(8). However, the mechanisms of agingassociated development of OA have not been clearly elucidated.…”
mentioning
confidence: 99%